1998
DOI: 10.1007/s000110050299
|View full text |Cite|
|
Sign up to set email alerts
|

Histamine release from rat mast cells induced by the metabolic activation of drugs of abuse into free radicals

Abstract: These results suggest that morphine, cocaine and methadone are activated into free radicals which produce membrane lipid perturbation and histamine release, suggesting that a massive release of mast cell histamine could be an additional risk factor in heroin and cocaine overdoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
0
31
1
Order By: Relevance
“…Continuous subcutaneous infusion of methadone for h or days at rates ranging between 0.75 and 34 mg/h produces local flushing and induration [20], possibly because the creation of free radicals during the metabolism of methadone provokes mast cell degranulation [21]. It seems unlikely that mast cell degranulation mediated local vasodilatation in the present study, because flares and wheals did not develop.…”
Section: Discussioncontrasting
confidence: 37%
“…Continuous subcutaneous infusion of methadone for h or days at rates ranging between 0.75 and 34 mg/h produces local flushing and induration [20], possibly because the creation of free radicals during the metabolism of methadone provokes mast cell degranulation [21]. It seems unlikely that mast cell degranulation mediated local vasodilatation in the present study, because flares and wheals did not develop.…”
Section: Discussioncontrasting
confidence: 37%
“…Free radicals derived from metabolites of unsaturated fatty acids participate in the induction of histamine release. 39,40) Another previous study reported that the inhibitory effect of curcumin on histamine release was closely related to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine-induced nonimmunologic mast cell degranulation and subsequent histamine release was reported previously [20]. Recently, Di Bello et al reported that in a presence of oxidative enzymes morphine is activated into free radicals, which produce membrane lipid perturbation leading to histamine release [21].…”
Section: Discussionmentioning
confidence: 99%